SISTEM INFORMASI PROMOSI UMKM BERBASIS WEBSITE PADA WILAYAH KECAMATAN ASEMBAGUS - Pahlevi, Syah Reza A.; Baijuri, Achmad; Azise, Nur (Fakultas Sains dan Teknologi, Universitas Ibrahimy, 2024)
The rapid advancement of technology is very beneficial for humans, it can even open up job and business opportunities. Entrepreneurs today must always keep up with market developments due to fast business competition. To achieve the expected profits, companies must apply the marketing concept effectively. This indicates that the company's marketing must be better managed and harmonised. The use of information technology is very important in promoting products to be marketed; one of them is MSME products promoted through a website built with PHP programming language and MySQL database. This system allows MSMEs to promote products, find out the results of sales reports, and make it easier for consumers to order, especially in the Asembagus sub-district area.